2019
DOI: 10.1002/jmv.25544
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation of potential inhibitors against vaccinia virus from 767 approved drugs

Abstract: The development of therapies for human smallpox is needed due to the increasing concern over the potential use of smallpox virus as a biological weapon. Here, we report a high-throughput screening for anti-smallpox virus drugs from a 767-smallmolecule library, employing two vaccinia virus (VACV) strains containing firefly luciferase (VTT-Fluc and VG9-Fluc) as surrogate viruses. Using an eight-point dose response format assay, 26 compounds of different pharmacological classes were identified with in vitro anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The VACV challenge model based on firefly luciferase expression 23 was used to assess the protection of mRNA-A-LNP and mRNA-B-LNP in mice. First, we investigated the passive protection of mRNA-A-LNP and mRNA-B-LNP immunized mouse sera (NT 50 : 6,284; 5,057), with sera from naive mice serving as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…The VACV challenge model based on firefly luciferase expression 23 was used to assess the protection of mRNA-A-LNP and mRNA-B-LNP in mice. First, we investigated the passive protection of mRNA-A-LNP and mRNA-B-LNP immunized mouse sera (NT 50 : 6,284; 5,057), with sera from naive mice serving as negative controls.…”
Section: Resultsmentioning
confidence: 99%
“…The other identified compounds did not show inhibition of viral infection in vivo. Interestingly, tranilast has been previously reported to have anti-smallpox activity (Wu et al, 2019), and it presented the highest anti-HAdV5 potency in vitro (SI > 75), but the compound did not show the expected efficacy in vivo. Several factors, such as the type of formulation, drug-enzyme interactions, or even interspecies differences in gastrointestinal adsorption, may affect drug efficacy.…”
Section: Discussionmentioning
confidence: 97%
“…It has been used in the treatment of inflammatory disease and several disease conditions including fibrosis and cardiovascular diseases and cancers. However, few studies reported an antiviral role for tranilast [ 23 ]. Although the concentration of tranilast used for the anti-HBV assay in this study is within the peak concentration in plasma after therapeutic dosage in patients (30–300 μM) [ 24 ], a relatively high dose (50–100 μM) was required to exert anti-HBV activity using hepatocyte culture compared to the tumor cell line ( Figure 2 and Figure 3 , Supplementary Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%